THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON CUSTOMER SATISFACTION AND ITS IMPACT TOWARD CUSTOMER LOYALTY (Survey Base on the perception of the Customer of BRI Bank in University of Brawijaya) - Zainurrafiqi, Zainurrafiqi; Sukoharsono, Eko Ganis; Hamid, Djamhur (Profit: Jurnal Adminsitrasi Bisnis, 2012)
The objective of this research is to analize and explain the effect of Customer Prospecting, Relations with Customers, Interactive Management, Understanding Customer Expectations, Empowerment, Partnerships, and Personalization On Customer Satisfaction and Its Impact on Customer Loyalty, and also to analize and explain the effect of Customer Satisfaction on Customer Loyalty. This research is conducted at BRI Bank in University of Brawijaya. The large samples that taken in this research were determined by using a formula of Slovin, the samples that could be taken are 99 persons. Meanwhile the sampling technique was done by using purposive sampling. Data Analysis Method is conducted by Descriptive Statistics Analysis and Inferential statistic analysis that is Path Analysis. The result of this research shown there is an effect between Customer Prospecting (X1) on Customer Satisfaction (Z) with Beta value is equal to 0.351 by a significance level of 0.000. There is an effect between Relations with Customers (X2) on Customer Satisfaction (Z) with Beta value is equal to 0.158 by a significance level of 0.010. There is an effect between Interactive Management (X3) on Customer Satisfaction (Z) with Beta value is equal to 0.161 by a significance level of 0.023. There is an effect between Understanding Customer Expectations (X4) on Customer Satisfaction (Z) with Beta value is equal to 0.272 by a significance level of 0.000. There is an effect between Empowerment (X5) on Customer Satisfaction (Z) with Beta value is equal to 0.145 by a significance level of 0.022. There is an effect between Partnerships (X6) on Customer Satisfaction (Z) with Beta value is equal to 0.208 by a significance level of 0.002. There is an effect between Personalization (X7) on Customer Satisfaction (Z) with Beta value is equal to 0.225 by a significance level of 0.000. There is an indirect effect between Customer Prospecting (X1) on Customer Loyalty (Y) with Beta value is equal to 0.146 by a significance level of 0.002. There is an effect between Relations with Customers (X2) on Customer Loyalty (Y) with Beta value is equal to 0.100 by a significance level of 0.017. There is an effect between Interactive Management (X3) on Customer Loyalty (Y) with Beta value is equal to 0.097 by a significance level of 0.042. There is an effect between Understanding Customer Expectations (X4) on Customer Loyalty (Y) with Beta value is equal to 0.111 by a significance level of 0.013. There is an effect between Empowerment (X5) on Customer Loyalty (Y) with Beta value is equal to 0.09 by a significance level of 0.030. There is an effect between Partnerships (X6) on Customer Loyalty (Y) with Beta value is equal to 0.13 by a significance level of 0.004. There is an effect between Personalization (X7) on Customer Loyalty (Y) with Beta value is equal to 0.103 by a significance level of 0.017. There is an effect between Customer Satisfaction (Z) on Customer Loyalty (Y) with Beta value is equal to 0.533 by a significance level of 0.000. Keywords: Customer Relationship Management (CRM), Customer Satisfaction, Customer Loyalty.